Advanced Transmission Electron Microscopy Imaging and Diffraction in Nanoscience - Zuo, Jian Min.; Spence, John C.H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2017)
This volume expands and updates the coverage in the authors' classic 1992 book, "Electron Microdiffraction." As the title implies, the focus of the book has changed from electron microdiffraction, or convergent beam electron diffraction, to electron nanodiffraction and the applications of electron diffraction from single crystals as well as general structure analysis of single crystals, powders, and nanostructures. Advanced Transmission Electron Microscopy provides a comprehensive treatment of theory and practice, and is written at a level suitable for advanced undergraduate students and graduate students and researchers in materials science, chemistry, and physics. Practical guides are provided for interpretation and simulation of electron diffraction patterns.
Introduction and historical background -- Electron Waves and Wave Propagation -- The geometry of electron diffraction patterns -- Kinematical Theory of Electron Diffraction -- Dynamical Theory of Electron Diffraction for Perfect Crystals -- Electron optics -- Lens aberrations and Aberration Correction -- Electron Sources -- Electron Detectors -- Instrumentation and experimental techniques -- Crystal symmetry -- Crystal structure and bonding -- Diffuse Scattering -- Atomic resolution electron imaging -- Imaging and characterization of crystal defects -- Strain Measurements and Mapping -- Structure of Nanocrystals, Nanoparticles and Nanotubes.
Keywords: Materials -- Analysis; Lasers; Nanochemistry; Nanoscience; Nanotechnology; Condensed matter; Characterization and Analytical Technique; Laser; Nanochemistry; Nanophysics; Nanotechnology; Condensed Matter Physics